Access and Repression in Korea - Salmenkari, Taru (Studia Orientalia Electronica, 2011)
This study assesses political opportunities available to civil society in the Republic of Korea. After democratisation, democracy movement activists simultaneously organised within civil society and entered political society, creating many links between the two. Street politics and violence have not decreased in relation to government responsiveness to civil society’s demands. Antiauthoritarian struggles lent demonstrations prestige, which, together with authoritarian influences in policing, has sustained a history of confrontation. Thus, Korea defies the theoretical assumption that political systems open to civil society initiatives use repression sparingly.